Identifying Glaucomatous Damage to the Macula. Issue 2 (February 2018) - Alluwimi, Muhammed S.; Swanson, William H.; King, Brett J.
Abstract : SIGNIFICANCE: Measurements of the macula have been increasingly used to diagnose and manage patients with glaucoma. Asymmetry analysis was clinically introduced to assess damage to the macular ganglion cells in patients with glaucoma, but its effectiveness is limited by high normal between-subject variability. PURPOSE: We aimed to reduce the high normal between-subject variability and improve the potential of asymmetry analysis to identify glaucomatous damage to the macula. METHODS: Twenty patients with glaucoma (aged 57 to 85 years) and 30 age-similar control subjects (aged 53 to 89 years) were recruited from a longitudinal glaucoma study. Participants were imaged with the Spectralis OCT using the posterior pole protocol; measurements of the averaged retinal thickness and ganglion cell layer (GCL) thickness were obtained. We established three zones per hemifield within the central ±9°, based on the lowest between-subject variability that we previously found and the course of retinal nerve fiber layer projections. The criteria for flagging abnormality were at least two contiguous zones when P < 5% or one zone when P < 1% with two-tailed tests. RESULTS: Between-subject variability of the asymmetry analysis for both retinal and GCL thicknesses remained lower than that of the average thickness across each zone in control subjects (F > 2.52, P < .01). Asymmetry analysis of retinal and GCL thicknesses flagged 16 and 18 of 20 patients, respectively. CONCLUSIONS: Between-subject variability was reduced in control subjects using the three zones; our criteria identified glaucomatous damage to the macula in most of the patients. We used high-density B-scans to confirm the patterns of the glaucomatous damage we found in this study.